(Re-)Defining critical digital literacy: what is it, and how should we teach it? - Harrison, Colin (Journal of China Computer-Assisted Language Learning, 2025)
This paper I attempt three things: to discuss the nature and definition of critical digital literacy, to share some of my research findings into the nature of critical digital literacy in both primary and secondary classrooms in the UK, and finally, to consider how to deal with the new challenges to critical digital literacy that artificial intelligence poses. In discussing critical digital literacy, I draw upon three theoretical frameworks as lenses through which to consider different aspects of critical literacy: first, the theories of Paulo Freire, which show how critical literacy does not simply read the world- it rewrites it, and it changes it; second, Coiro’s perspective on the epistemological mutations of the concept of “truth” that have been brought about and accelerated by the Internet; third, the perspectives of Mikhail Bakhtin, who had much to say about the nature of learning, in particular arguing that all learning is dialogic, and also that many questions to which we might seek definitive answers are in the end “unfinalizable”.